The Impact of a Shortage of Pharmacy-Prepared Ephedrine Syringes on Intraoperative Medication Use. (August 2015) - Ladha, Karim S.; Nanji, Karen C.; Pierce, Eric; Poon, K. Trudy; Hyder, Joseph A.
<x xml:space="preserve">Abstract</x> BACKGROUND: Anesthesia-related medication shortages have become increasingly common in the United States. We tested whether a local shortage of pharmacy-prepared ephedrine syringes, replaced by provider-prepared ephedrine, was associated with provider-level changes in ephedrine and phenylephrine use and patient-level changes in intraoperative hemodynamics. METHODS: Consecutive patients undergoing general and orthopedic surgery at a tertiary care center were included 1 month before and 1 month after the start of the pharmacy-prepared ephedrine syringe shortage. Lowest mean arterial blood pressure and slowest heart rate were obtained as measures of hemodynamics. Adjusted associations were tested using mixed-effects regression with repeated measures. RESULTS: Three hundred four patients before the shortage and 298 patients after the shortage began were included. The administration of at least 1 bolus of ephedrine was significantly more common before versus during the shortage (148/304 [48.7]% vs 117/298 [39.3]%; P = 0.0199). After adjusting for age, sex, ASA physical status, surgery type, anesthesia provider, and operative duration, patients were significantly less likely to receive ephedrine during the shortage (relative risk [RR] = 0.78 [95% confidence interval CI, 0.61–0.96]; P = 0.0198) and more likely to receive a phenylephrine bolus (RR = 1.27 [95% CI, 1.02–1.51]; P = 0.0357). Patient hemodynamics assessed by slowest heart rate or lowest mean arterial blood pressure did not differ significantly during the shortage. CONCLUSIONS: There was an alteration in medication administration patterns during a shortage of pharmacy-prepared syringes. Changes in ephedrine and phenylephrine use were noted; however, patient hemodynamics remained comparable. Provider use patterns were sensitive even to a relative and not absolute medication shortage as observed in this study.